History of spinal neurosurgery and spine societies (2020)
Historically, spine and spinal cord surgery have been an integral part of neurosurgery. It was always a part of the neurosurgery education and practically a significant part of neurosurgeons’ daily work. However, spine societies have mostly been pioneered by orthopedic spine surgeons. It’s only in the last 4 decades that neurosurgeons are also forming spine societies. The term “Neurospine” becomes more popular and used by many authors, institutions during the last decades, although it is not widely used in North America. There are specific reasons for its popularity: (1) It is like a combination of neurosurgery and spine surgery. Neurosurgeons widely prefer to use it. (2) It has a sense inside to remind patients that the spine is with neurological structures. “Neurospine Surgery” is also used in the sense of a combination of “neuroscience” and “spine”. There are at least 2 journals with this theme, i.e., “Neurospine” and “Journal of Neurosurgery Spine.” [1] In this paper, a brief history of spine surgery and spine-related societies is discussed. We aimed to create a global summary of neuro spine with spinal neurosurgeons’ perspectives from other parts of the world and comment on the world's current condition.